Alḥamdulillāh kih risālah majmūʻah-yi ḥavālahjāt-i maẕhab-i Shīʻah va Rāfi̤zī, al-mausūm bah, Cashmah-yi nūr afzā : sharḥ Āʼīnah-yi Shīʻah numā - Uvaisī, Fai̤z Aḥmad, 1932?- (Maktabah-yi Uvaisiyah Ri̤zviyah, 1978)
A polemic against the religious beliefs of the Shia Sect of Islam, by a Sunni scholar.